Time-resolved spectral-image laser-induced breakdown spectroscopy for precise qualitative and quantitative analysis of milk powder quality by fully excavating the matrix information. (30th August 2022) - Zhang, Deng; Nie, Junfei; Niu, Xuechen; Chen, Feng; Hu, Zhenlin; Wen, Xuelin; Li, Yuqiong; Guo, Lianbo
Graphical abstract: Highlights: A novel method named time-resolved spectral-image laser-induced breakdown spectroscopy (TRSI-LIBS) was proposed. TRSI-LIBS not only uses the intensity information of spectra, but also can effectively excavate the matrix information. The time-resolved spectra used by TRSI-LIBS are less affected by fluctuations and have strong robustness. TRSI-LIBS can effectively improve the performance of qualitative and quantitative analysis models for milk powder quality. Abstract: A novel and effective method named time-resolved spectral-image laser-induced breakdown spectroscopy (TRSI-LIBS) was proposed to achieve precise qualitative and quantitative analysis of milk powder quality. To verify the feasibility of TRSI-LIBS, qualitative and quantitative analysis of milk powder quality was carried out. For qualitative analysis of foreign protein adulteration, the accuracy of models based on TRSI-LIBS was higher than those based on LIBS, with an accuracy improvement of about 5% to 10%. For the quantitative analysis of foreign protein adulteration and element content, the quantitative analysis models based on TSRI-LIBS also had better effect. For instance, limit of detection (LOD), determination coefficient of prediction (R 2 p), root-mean-square error of prediction (RMSEP) and average relative error of prediction (AREP) of quantitative model of calcium (Ca) content based on TRSI-LIBS improved from 1.47 mg/g, 0.95, 0.35 mg/g and 23.29% to 0.81 mg/g, 0.98, 0.20 mg/g and 12.60%.